The functional properties of alcalase produced threadfin bream (Nemipterus Japonicus) protein hydrolysate / Normah I. ... [et al.] - I, Normah; B, Jamilah; S, Nazamid; CM, Yaakob (Faculty of Applied Sciences, 2004)
This study was carried out to determine the functional properties of threadfin bream (Nemipterus japonicus) hydrolysate. The hydrolysate exhibited more than 95% solubility over a wide pH range from 2.5 to 11 with low emulsifying property. Foam ability was improved in the hydrolysate as compared to the unhydrolysed threadfin bream muscle. However, the foam was unstable over time.